The contribution meaning of life toward subjective well-being of adolescents in Minangkabau Etnic - Amalianita, Berru; Kusaini, Utami Niki (Universitas Islam Negeri Raden Intan Lampung, 2023)
The notion of “meaning of life” carries substantial importance when considering the holistic state of being throughout different phases of one’s existence. Adolescents with the cognitive ability to comprehend and determine the significance of existence frequently exhibit a feeling of contentment and overall welfare in their encounters. This research endeavour aimed to investigate the impact of life goal interpretation on the subjective well-being of adolescents of Minangkabau ethnicity. This investigation is quantitative and employs correlational methodology. Adolescents belonging to the Minangkabau ethnic group were assembled as subjects for this study. This research utilized a sample of 182 adolescents from the Minangkabau tribe. The research employs a subjective well-being instrument derived from Dineer, comprising 56 items, to assess cognitive and affective dimensions. Subsequently, elements of creative, experience, and attitude value are evaluated using a meaning of life instrument developed from Victor Frank’s theory, comprising 47 items. Methods for analyzing data consist of descriptive, correlation, and straightforward regression tests. Numerous studies indicate that adolescents consider life objectives of the utmost importance. On the other hand, adolescents of Minangkabau ethnicity should pay close attention to their subjective well-being. With a variance of 42.7%, the meaning of life is substantially impacts the subjective well-being of Minangkabau adolescents. These results suggest that the notion of life’s purpose significantly affects an individual’s subjective well-being. Investigating and comprehending the purpose of existence can cultivate positive emotions and generate sentiments of contentment and joy among adolescents.